2002
DOI: 10.1108/02686900210437471
|View full text |Cite
|
Sign up to set email alerts
|

The stock market reaction to fraudulent financial reporting

Abstract: Explores the impact that recent fraudulent financial reporting has had on the capital markets. Attempts to examine the stock market reaction, both to return and risk, to fraudulent financial reporting that has occurred in major corporations during the decade 1990-1999. Finds that capital market impact is significant in dollar terms with strong negative announcement effects the day before and on the day of a news event. Concludes that auditor and regulator vigilance needs to be strongly maintained in monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Fraudulent financial reporting and its impact on capital markets was explored by Cox and Weirich (2002). The study found a significant negative announcement effect on the day before and on the day of a news event.…”
Section: Existing Evidence On the Role Of Newsmentioning
confidence: 98%
“…Fraudulent financial reporting and its impact on capital markets was explored by Cox and Weirich (2002). The study found a significant negative announcement effect on the day before and on the day of a news event.…”
Section: Existing Evidence On the Role Of Newsmentioning
confidence: 98%
“…From the long-term perspective, CSR can promote the competitiveness of companies. Fraudulent financial reporting has had a strong negative effect on the capital markets [23]. As a kind of corporate social irresponsibility, corporate crime has not only an impact on the reputation of companies, but also causes the loss of financial performance and the incontinence of investors [24].…”
Section: A Influence Of Rse On Sme Performancementioning
confidence: 99%
“…It is regarded as a powerful financial tool in efficient market hypothesis research. To this effect many researcher globally have successfully utilised this tool, for example though not exhaustive, Aharony and Swary (1980), Bowman (1983), Cox and Weirich (2002), Dey and Radhakrishna (2008), and Laidroo (2008). In South Africa researchers like Bhana (1995Bhana ( /1996Bhana ( , 2005Bhana ( , 2007a), Mushidzi and Ward (2004) and Ward and Muller (2010) successfully utilised the tool to assess the information content of announced corporate event.…”
Section: Event Studiesmentioning
confidence: 99%